Separation and characterization of inner and outer envelope membranes of pea chloroplasts - Cline, Kenneth (1981)
A procedure for purifying the chloroplast envelope subfractionates it into two membrane fractions of comparable quantities. This procedure differs from previous ones in that the chloroplasts are ruptured by freezing and thawing in hypertonic medium rather than by osmotic shock. The two membrane fractions have qualitatively similar polar lipid compositions but differ in their content of individual lipids, specifically monogalactosyldiacylglycerol and phosphatidylcholine. The two fractions also differ in their constituent polypeptides and in their appearance when examined by electron microscopy. The light (density = 1.08 g/ml) and heavy (density = 1.13 g/ml) membrane fractions have been tentatively identified as the outer and inner envelope membranes, respectively.